Integrating ESP32 and VESC-Controlled BLDC Motors in Cart Inverted Pendulum Design - Ida Lailatul Fitria; Indrazno Siradjuddin; Ferdian Ronilaya; Gillang Al Azhar; Zakiyah Amalia; Budhy Setiawan (IRDH International Journal of Technology, Agriculture and Natural Sciences, 2025)
This paper presents the design and implementation of a cart inverted pendulum system using an ESP32 microcontroller and a brushless DC (BLDC) motor with a Vedder Electronic Speed Controller (VESC). The cart inverted pendulum is a well-known benchmark problem in control theory due to its nonlinear, unstable, and underactuated nature. The ESP32 System-on-Chip (SoC) is chosen for its high processing power, low-cost, and low-power characteristics, making it suitable for real-time control applications. The BLDC motor, coupled with the VESC, provides efficient and precise actuation for the cart inverted pendulum system. The VESC, an open-source motor controller, offers advanced control algorithms and hardware upgrades that enable accurate current, position, and speed control. Integrating the ESP32 and BLDC motor with VESC in the cart inverted pendulum design addresses the need for more efficient and costeffective solutions in this field. The paper discusses the hardware design, software design using FreeRTOS and serial communication, and presents the results of the hardware and software evaluation. The findings of this study contribute to the advancement of control theory and its applications in various domains, such as robotics and electric vehicles.